Strategies as Resource Terms, and their Categorical Semantics - Blondeau-Patissier, Lison; Clairambault, Pierre; Auclair, Lionel Vaux (Logical methods in computer science, 2025)
As shown by Tsukada and Ong, simply-typed, normal and eta-long resource terms correspond to plays in Hyland-Ong games, quotiented by Melliès' homotopy equivalence. The original proof of this inspiring result is indirect, relying on the injectivity of the relational model w.r.t. both sides of the correspondence -- in particular, the dynamics of the resource calculus is taken into account only via the compatibility of the relational model with the composition of normal terms defined by normalization. In the present paper, we revisit and extend these results. Our first contribution is to restate the correspondence by considering causal structures we call augmentations, which are canonical representatives of Hyland-Ong plays up to homotopy. This allows us to give a direct and explicit account of the connection with normal resource terms. As a second contribution, we extend this account to the reduction of resource terms: building on a notion of strategies as weighted sums of augmentations, we provide a denotational model of the resource calculus, invariant under reduction. A key step -- and our third contribution -- is a categorical model we call a resource category, which is to the resource calculus what differential categories are to the differential lambda-calculus.